PENGARUH DISIPLIN BELAJAR SISWA TERHADAP HASIL BELAJAR MATEMATIKA DI KELAS TINGGI SD NEGERI KELURAHAN PALANRO KABUPATEN BARRU - Djabba, Rasmi; Mukhlisa, Nurul; Ferdiansyah, Rian (Universitas Negeri Medan, 2022)
This study is a quantitative survey method which aims to determine whether there is an influence of learning discipline on the learning outcomes of high grade students of SD Negeri Palanro Village. Learning discipline is the independent variable, while the learning achievement of mathematics are the dependent variable in this study. The population in this study were the high-class students of SD Negeri Palanro, Barru Regency, totaling 120 students, while the sample was 95 students. The research data collection technique used a questionnaire and mid-semester test scores for odd semester mathematics subjects for the 2021/2022 academic year. The data analysis technique used is simple linear regression analysis and significance test. Based on the results of the descriptive analysis, the learning discipline was classified as very good with a percentage of 62.1% and the students' mathematics learning outcomes were classified as good with a percentage of 60%. From the results of inferential analysis obtained the value of sig. 0.020 < 0.05 or H0 is rejected and H1 is accepted, which means that learning discipline has a positive and significant effect on students' mathematics learning outcomes.